Investigation of phenolic compounds of Primula veris L. - Shostak, L. G.; Marchyshyn, S. M.; Kozachok, S. S.; Karbovska, R. V. (Journal of Education, Health and Sport, 2016)
Shostak L. G., Marchyshyn S. M., Kozachok S. S., Karbovska R. V. Investigation of phenolic compounds of Primula veris L. Journal of Education, Health and Sport. 2016;6(5):424-432. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.56701 http://ojs.ukw.edu.pl/index.php/johs/article/view/3646 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.05.2016. Revised 25.05.2016. Accepted: 25.05.2016. UDC 581.192:547.56:581.689 INVESTIGATION OF PHENOLIC COMPOUNDS OF PRIMULA VERIS L. 1L. G. Shostak, 1S. M. Marchyshyn, 1S. S. Kozachok, 2R. V. Karbovska 1I. Horbachevsky Ternopil State Medical University 2SE «Ukrmetrteststandard» Summary It was established the presence and determined the quantity content of individual phenolic compounds in rhizomes with roots, leaves, flowers of Primula veris L. such as: apigenin, rosmarinic, p-coumaric, ferulic, ellagic, gallic acids, scopoletin, gallocatechin, epigallocatechin, catechin, epicatechin, catechin gallate, epicatechin gallate. The highest amount of hydroxycinnamic acids identified in the leaves and the constituents of tannins –rhizomes with roots. Keywords: rhizomes with roots, leaves, flowers of Primula veris L., hydroxycinnamic acids, constituents of tannins, coumarins, HPLC.